IMPLEMENTATION OF GOVERNANCE IN ZAKAT INSTITUTIONS: CASE STUDY OF THE NATIONAL AMIL ZAKAT AGENCY OF HULU SUNGAI SELATAN REGENCY - Rizky Fadhillah; Ahmad Miftahurrahman (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2025)
This study aims to evaluate the implementation of governance of the National Amil Zakat Agency in Hulu Sungai Selatan Regency by using three assessment tools: Zakat Core Principles, Sharia Compliance Index of Zakat Management Organization, and financial ratio analysis. Descriptive qualitative methods were used, with data collected through observation, in-depth interviews, documentation, and structured questionnaires. The findings show that the implementation of Zakat Core Principles is rated “good” with a score of 0.65, which indicates a generally effective governance structure, especially in zakat collection and legal compliance, although operational control and internal audit mechanisms are still weak. The Shariah Compliance Index of Zakat Management Organizations resulted in a score of 0.76, which indicates that the institution's operations largely comply with shariah principles. The financial ratio analysis resulted in a performance score of 1.98, reflecting high operational efficiency and effective allocation of funds to beneficiaries. However, the growth ratio indicates a need for strategic improvement in the development of zakat funds. Overall, this study contributes to the strengthening of sharia-compliant and accountable zakat governance, and provides strategic input for regional zakat institutions to implement professional and transparent management practices.